Oxytocin mediates neuroprotection against hypoxic-ischemic injury in hippocampal CA1 neuron of neonatal rats. (1st April 2021) - Wu, Zhihong; Xie, Changning; Kuang, Haixia; Wu, Jian; Chen, Xiao; Liu, Huibao; Liu, Tao
Abstract: Neonatal hypoxic-ischemic encephalopathy (NHIE) is one of the most prevalent causes of death during the perinatal period. The lack of exposure to oxytocin is associated with NHIE-mediated severe brain injury. However, the underlying mechanism is not fully understood. This study combined immunohistochemistry with electrophysiological recordings of hippocampal CA1 neurons to investigate the role of oxytocin in an in vitro model of hypoxic-ischemic (HI) injury (oxygen and glucose deprivation, OGD) in postnatal day 7–10 rats. Immunohistochemical analysis showed that oxytocin largely reduced the relative intensity of TOPRO-3 staining following OGD in the hippocampal CA1 region. Whole-cell patch-clamp recording revealed that the OGD-induced onset time of anoxic depolarization (AD) was significantly delayed by oxytocin. This protective effect of oxytocin was blocked by pretreatment with [d(CH2)51, Tyr (Me)2, Thr4, Orn8, des-Gly-NH29] vasotocin (dVOT, an oxytocin receptor antagonist) or bicuculline (a GABAA receptor antagonist). Interestingly, oxytocin enhanced inhibitory postsynaptic currents in CA1 pyramidal neurons, which were abolished by tetrodotoxin or dVOT. In contrast, oxytocin had no effect on excitatory postsynaptic currents but induced an inward current in 86% of the pyramidal neurons tested. Taken together, these results demonstrate that oxytocin receptor signaling plays a critical role in attenuating neonatal neural death by facilitating GABAergic transmission, which may help to regulate the excitatory-inhibitory balance in local neuronal networks in NHIE patients. Highlights: Oxygen-glucose deprivation exposure leads to neuronal death. The neuronal death is reduced by oxytocin. Oxytocin delays the onset of anoxic depolarization. Neuroprotective effects of OT are mediated by oxytocin receptor and GABAA receptor.